Land and Atmospheric Drivers of the 2023 Flood in India - Kushwaha, Anuj Prakash; Solanki, Hiren; Vegad, Urmin; Mahto, Shanti Shwarup; Mishra, Vimal (Earth and space science (Hoboken, N.J.), 2024)
Floods in India are recurring natural disasters resulting from extreme precipitation during the summer monsoon season (June–September). The recent flood in North India in July 2023 caused substantial damage to lives, agriculture, and infrastructure. However, what led to the 2023 North India flood and the role of atmospheric and land drivers still need to be examined. Using in situ observations, satellite data, and ERA5 reanalysis combined with hydrological and hydrodynamical modeling, we examine the role of land and atmospheric drivers in flood occurrence and its impacts. Extreme precipitation in a large region during 7–10 July 2023 created favorable conditions for the flood in the hilly terrains and plains of north India. More than 300 mm of precipitation fell in just 4 days, which was eight times higher than the long‐term average (2001–2022). Anomalously high moisture transport over northern India was recorded on 7 July 2023, making atmospheric conditions favorable for intense landfall. Increased column water vapor and specific humidity at different pressure levels confirmed the continuous moisture presence before the extreme rainfall that caused floods in northern India from 7 to 12 July 2023. Atmospheric and land (high antecedent soil moisture) conditions contributed to a more than 200% rise in streamflow at several gauge stations. Satellite‐based flood extent shows a considerable flood inundation that caused damage in the Sutlej and Yamuna River basins. Our findings highlight the crucial role of the favorable land and atmospheric conditions that caused floods and flash floods in north India in July 2023. Plain Language Summary In July 2023, North India experienced a severe flood that caused significant damage to lives, agriculture, and infrastructure. However, the exact causes of this flood have yet to be examined. Using in situ, satellite, and reanalysis data, we examined the drivers of the flood. Favorable atmospheric and land conditions created a unique situation that led to a significant flood in north India. For instance, extreme precipitation during 7–10 July enhanced antecedent soil moisture conditions in the hilly and plain regions. Anomalously high moisture transport caused intense rainfall, which, combined with high soil moisture, produced high runoff and streamflow conditions. Flood inundation caused damage to the Sutlaj and Yamuna river basins. Our findings show the need to monitor soil moisture and atmospheric processes for early warning of floods in hilly regions. Key Points The flood in North India in July 2023 caused substantial damage to lives, agriculture, and infrastructure Anomalously high moisture transport over northern India created atmospheric conditions favorable for intense landfall High antecedent soil moisture and extreme precipitation caused the north India flood in 2023